2003
DOI: 10.1002/etc.5620220418
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous photochemical reactions of decabromodiphenyl ether

Abstract: Brominated diphenyl ethers are a major class of brominated flame retardants, with production of decabromodiphenyl ether (DBDPE) contributing significantly to this total. Although little is known about the mechanisms and rates of DBDPE decay in the natural environment, photochemical transformation is often suggested as a potentially important fate process. In this study, photochemical reactions of DBDPE precipitated onto hydrated surfaces (quartz glass, silica particles, and humic acid-coated silica particles) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Photolysis of higher brominated PBDEs by UV-light and sunlight have been observed in the past with formation of lower brominated congeners through sequential debromination (Hua et al, 2003; Söderström et al, 2004). Microbial debromination of deca- and octa-BDEs have also been observed under anaerobic conditions (He et al, 2006; Lee and He, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Photolysis of higher brominated PBDEs by UV-light and sunlight have been observed in the past with formation of lower brominated congeners through sequential debromination (Hua et al, 2003; Söderström et al, 2004). Microbial debromination of deca- and octa-BDEs have also been observed under anaerobic conditions (He et al, 2006; Lee and He, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Reductive debromination is probably the main mechanism of photodegradation of PBDEs (1518, 43). It has been suggested that the homolytic dissociation of aryl-Br bonds leads to the debromination of PBDEs generating aryl and bromine radicals and subsequently lower brominated DEs, PBDFs and other degradation products (18, 43).…”
Section: Resultsmentioning
confidence: 99%
“…Under certain conditions, antimony trioxide can act as a strong photosensitizer. Silica can also accelerate photodegradation of Deca 25…”
Section: Halogenated Flame Retardantsmentioning
confidence: 99%